An Analytical Report of Phytochemical Constituents, Pharmacological Potential, and Toxic Effects of Radish - Ishrat Younus, Afshan Siddiq, Sadia Gousia Baig, Rafia Sadaf, Talha Bin Fayyaz, Noor Ul Ain, Zubia Begum, Arslan Ahmer (Pakistan Journal of Medical & Health Sciences, 2023)
Vegetables have great significance and importance as they are not only useful as food but on the other hand, vegetables are a vital source in the treatment and prevention of various ailments, a powerful source of minerals, vitamins, antioxidants, fibers, and amino acids, therefore, help to buildup and heal the body. Mainly concerning cruciferous vegetables, have been famous for marked effects of cardio-protective, antimicrobial, and anti-carcinogenic. The environments of Pakistan are amicable for vegetable production. Raphanus sativus generally named radish is a widespread plant all over the world belongs to the Brassicaceae family. Edible R sativus L. Var. caudatus are green color seed pods, utilized for properties attributed to Raphanus. Different chemical constituents are identified from radish. Various researches show that the whole radish plant has significant pharmacological activity. The current review expands ontypes, phytochemical components, and pharmacological potential and toxic outcomes of the radish plant Keywords: Radish, varieties, constituents, pharmacology, uses, toxicity